Decolonizing Digital Learning in Ghana: Artificial Intelligence, Local Knowledge, and Educational Futures - Ayishetu Pantah (International Journal of Social Science, Education, Communication and Economics (SINOMICS Journal), 2025)
The rapid expansion of digital learning and artificial intelligence (AI) has significantly transformed educational systems worldwide, including in Ghana. However, the integration of digital technologies into education also raises critical concerns regarding epistemological inequality, technological dependency, and the marginalization of indigenous knowledge systems. This study aims to critically examine digital learning in Ghana through a decolonial perspective by exploring the relationship between artificial intelligence, local knowledge, and future educational transformation. The study employed a qualitative conceptual approach based on critical literature review and decolonial theoretical analysis. Data sources consisted of scholarly articles, academic books, policy reports, and international publications related to digital learning, AI in education, indigenous knowledge systems, and postcolonial educational transformation. The findings reveal that contemporary digital learning systems frequently reproduce colonial epistemologies through linguistic dominance, curriculum standardization, algorithmic bias, and dependency on externally developed technological infrastructures. Indigenous languages and local knowledge systems remain underrepresented within mainstream educational technologies, limiting epistemic inclusivity and cultural relevance. Nevertheless, the study also identifies the transformative potential of culturally responsive AI, multilingual digital learning environments, and indigenous knowledge integration in constructing more equitable educational futures. The study concludes that decolonizing digital learning in Ghana requires the reconstruction of educational technologies grounded in epistemic justice, cultural dignity, local participation, and technological sovereignty. This article contributes to contemporary discussions on decolonial education, ethical AI, and digital transformation within the Global South by positioning digital learning as both a technological and epistemological arena of struggle.